2017
DOI: 10.5433/1679-0359.2017v38n4p1973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovarian tissue storage in Morus nigra extract on the morphology and DNA fragmentation of ovine preantral follicles

Abstract: This study demonstrated the effect of Morus nigra leaf extract during ovine ovarian tissue transportation on the survival and apoptosis of preantral follicles in vitro. High Performance Liquid Chromatography (HPLC) was used to determine the fingerprint chromatogram of the crude ethanolic extract. Four pairs of ovaries from four sheep were collected. The ovarian cortex was fragmented and one fragment was fixed in 10% buffered formaldehyde and processed for histological and TUNEL analyses (fresh control). The ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A previous study has shown that the ethanolic extract of M. nigra , which was the same used in the current work, contains compounds with antioxidant properties: isoquercetin (22.3 ± 3.02 μg/ml), rutin (5.05 ± 1.3 μg/ml) and kaempferitrin (Cavalcante et al., ). We should take into account that environments in which the plant develops (temperature, relative humidity, solar radiation, soil) exert a direct influence on the chemical composition of the extracts (Floss, ; Suarez, Gil, & Lorenzo, ).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…A previous study has shown that the ethanolic extract of M. nigra , which was the same used in the current work, contains compounds with antioxidant properties: isoquercetin (22.3 ± 3.02 μg/ml), rutin (5.05 ± 1.3 μg/ml) and kaempferitrin (Cavalcante et al., ). We should take into account that environments in which the plant develops (temperature, relative humidity, solar radiation, soil) exert a direct influence on the chemical composition of the extracts (Floss, ; Suarez, Gil, & Lorenzo, ).…”
Section: Discussionmentioning
confidence: 85%
“…The leaves were dried in an oven at 40°C and pulverized and extracted at room temperature with 95% ethanol (Vetec, Duque de Caxias‐RJ, Brazil) for 72 hr. The extract was dried at 45°C for some hours under vacuum using rotavapor and the yield was approximately of 10% obtaining the crude ethanolic extract (CEE) of the leaves of M. nigra (Cavalcante et al., ), which was dissolved in 0.9% saline solution, corresponding to concentrations of 0.025, 0.05 or 0.1 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations